1999
DOI: 10.1016/s0009-9236(99)70031-7
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal secretion of intravenous talinolol is inhibited by luminal R-verapamil*

Abstract: Intravenously administered talinolol is actively secreted into the human small intestine. This secretion is reduced by the intraluminal supply of the P-glycoprotein modulating drug R-verapamil. This gives further rationale for P-glycoprotein-mediated intestinal drug secretion as a cause for incomplete oral bioavailability and for drug interactions during intestinal absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 17 publications
1
67
0
Order By: Relevance
“…So far, the b-blocking agent talinolol is the only compound for which a signi®cant secretion into the gut lumen in man has already been demonstrated. 11,12 The drug is subjected to minor metabolism, less than 1% is excreted into urine in form of hydroxylated metabolites. 13±15 It is unknown whether metabolites are excreted by other pathways (e.g., biliary, intestinal).…”
Section: ±10mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the b-blocking agent talinolol is the only compound for which a signi®cant secretion into the gut lumen in man has already been demonstrated. 11,12 The drug is subjected to minor metabolism, less than 1% is excreted into urine in form of hydroxylated metabolites. 13±15 It is unknown whether metabolites are excreted by other pathways (e.g., biliary, intestinal).…”
Section: ±10mentioning
confidence: 99%
“…However, information on the suitability of racemic talinolol to predict P-gp expression is still limited by contradictory results on the chirality of talinolol disposition. 12,16 If the P-gp dependent transport of talinolol would be stereoselective, then upregulation of the carrier by rifampicin should result in adequate differences of R() and S(À) talinolol disposition. Therefore, we reassessed the serum samples of a recently published interaction study with rifampicin to measure pharmacokinetics of talinolol enantiomers.…”
Section: ±10mentioning
confidence: 99%
“…A similar study used four antibodies directed against MDR1 in endocardium, mid-myocardium and epicardium (Pavelic et al, 1993). Only mid-myocardium revealed weak immunostaining for three of the antibod- Kartner et al (1983), Ueda et al (1987), Pastan et al (1988), de Lannoy andSilverman (1992), Hendricks et al (1992), Peters and Roelofs (1992), Karlsson et al (1993), de Graaf et al (1996, Sparreboom et al (1997), Kim et al (1998), Gramatte and Oertel (1999), Verschraagen et al (1999) Cole et al (1992Cole et al ( , 1994, Flens et al (1996), Sharp et al (1998) Not determined Heart, skeletal muscle, liver…”
mentioning
confidence: 98%
“…Because placental ABCB1 expression decreases with advancing gestation age whereas ABCC2 undergoes gestational maturation, we hypothesized that ABCC2 in term placentas may be more important than ABCB1 for the transfer of drugs that are substrates of both carriers (Meyer zu Schwabedissen et al, 2005;Sun et al, 2006). A suitable probe drug to evaluate function of ABCB1 and ABCC2 in humans is the nonmetabolized ␤ 1 -selective blocker talinolol, which is a high affinity substrate of ABCB1 as evidenced by in vitro experiments and pharmacokinetic studies in humans and of ABCC2 as concluded from major changes in disposition in Abcc2-deficient GY/ TR Ϫ rats (Spahn-Langguth et al, 1998;Gramatté and Oertel, 1999;Westphal et al, 2000;Bernsdorf et al, 2003). ␤ 1 -Selective blockers are used in the treatment of hypertension during pregnancy (Magee et al, 2000).…”
mentioning
confidence: 99%